1998
DOI: 10.1046/j.1525-1500.1998.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for In Vitro Anti-Tumor-Promoting Activities of Edible Plants from Indonesia

Abstract: A total of 135 methanol extracts from 48 plant families (107 species) of edible Indonesian plants were screened for their in vitro anti-tumor-promoting activities using the tumor promoter 12-O-hexadecanoylphorbol-13-acetate (HPA)induced Epstein-Barr virus (EBV) activation test in Raji cells. Examined at a concentration of 200 mg/ml, 71% of the extracts inhibited EBV activation by 30% or more. The rate is comparable to the rate observed in our previous tests of edible Thai (60%) plants and much higher than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…This effect could be due to the sensitivity of cell lines to the nature of active compounds present in the extracts and could represent a tissue-specific response. In the previous study using Raji cells, it was reported that extract of K. galanga was less active compared to the other species (Murakami et al, 1998) and its ethanol extract showed inhibitory activity at a concentration of 320 mg/ml (Vimala et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This effect could be due to the sensitivity of cell lines to the nature of active compounds present in the extracts and could represent a tissue-specific response. In the previous study using Raji cells, it was reported that extract of K. galanga was less active compared to the other species (Murakami et al, 1998) and its ethanol extract showed inhibitory activity at a concentration of 320 mg/ml (Vimala et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Screening for antitumor activity of some members of Zingiberaceae has been conducted using activated Epstein Bar Virus (EBV) on Raji cells (Murakami et al, 1998;Vimala et al, 1999). In this study we screened ethanol extracts of eleven species of Indonesian Zingiberaceae most frequently used for traditional medicine and in food, using two established cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Much attention has been paid to explore any potential antitumor agents in edible plants, for future use in humans. Amongst many medicinal plants screened, the methanolic extract of P. speciosa seeds demonstrated a moderate antimutagenic activity in the Ames test [34], while in inhibition assay of Epstein-Barr virus (EBV), the antitumor promoting activity of the seeds was considered as weakly active [50]. Nevertheless, it had been reported that consumption of the raw seeds reduced the incidence of esophageal cancer in Southern Thailand [51].…”
Section: Properties Of P Speciosamentioning
confidence: 99%
“…In fact, report has shown significant cholesterollowering effect and improvement in glucose tolerance in animals treated with unripe plantain flour (Usha and Vijayammal, 1991). Furthermore, there are indications that plantain flakes can be used as a safe and costeffective treatment for diarrhea, hyperoxaluric urolithiasis and colorectal cancer (Poonguzhali and Chegu, 1994;Emery et al, 1997;Lohsoonthorn and Danvivat, 1995;Deneo-Pellerini et al, 1996;Murakami et al, 1998). Moreover, reports have indicated that treatment with plantain significantly decreased the systolic, diastolic and arterial blood pressure during cold stress-induced hypertension (Sarkar et al, 1999) Despite the aforementioned health benefits, plantain undergoes natural or induced ripening which brings about an inevitable alteration in its organoleptic and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%